Revisiting the problem of using methylene blue as a model pollutant in photocatalysis: The case of InVO4/BiVO4composites - Dariusz Mitoraj (2018)
© 2018 Elsevier B.V. Evaluation of photocatalytic activity towards oxidative degradation of organic pollutants is of crucial importance in heterogeneous photocatalysis. In this study, we address the problem of using a visible-light absorbing dye, methylene blue, as a model pollutant in photocatalytic investigations based on experiments using visible light-responsive InVO4/BiVO4composite photocatalyts. We found that InVO4/BiVO4composites exhibit photoactivity in oxidative decomposition of MB under visible light, but no degradation was found in case of other dyes (e.g., rhodamine B or methyl orange) or transparent organic pollutants (e.g., 4-chlorophenol and diethyl phthalate). Detailed mechanistic studies demonstrate that the mechanism of photocatalytic degradation of MB depends on excitation light energy. If the InVO4/BiVO4composite is excited exclusively (400 nm < λ < 500 nm), direct photocatalytic oxidation of MB occurs. Surprisingly, wavelength-resolved photocurrent measurements indicated that the degradation of MB under long-wavelength irradiation (λ > 560 nm), where MB can be excited but the InVO4/BiVO4photocatalyst itself cannot, is not caused by the indirect mechanism involving sensitization and injection from the MB excited state to the conduction band of the photocatalyst. Instead, in this range the oxidation of MB is initiated by singlet oxygen formed via energy transfer from the excited MB to triplet oxygen, a degradation mechanism hitherto neglected in the literature. More generally, our study highlights the very peculiar photochemistry of MB in heterogeneous photocatalysis, and leads to the conclusion that MB is completely unsuitable for photocatalytic testing under visible light, and its use as a model pollutant should be definitely discouraged.